PENGARUH PROFITABILITAS, SOLVABILITAS, AUDIT TENURE DAN REPUTASI KAP TERHADAP AUDIT DELAY PADA PERUSAHAAN SEKTOR MANUFAKTUR BEI PERIODE 2020-2021 - Windy Tosiana; Endang Sri Utami (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2023)
Audit delay is the amount of time that must pass before the audited financial statements can be completed. This amount of time is based on the number of days that must elapse before the independent auditor can complete his report on the annual financial statements. This study aims to determine the effect of profitability, solvency, audit tenure, and KAP reputation on the length of time auditing manufacturing companies on the IDX for the 2020-2021 period. The purposive sampling method was used to select the sample for this study. The use of multiple regression analysis is used in conducting data analysis. According to the findings of this study, audit delay is not at all affected by company solvency or audit tenure; on the other hand, KAP's profitability and reputation affect audit delay.